Sistem Pendukung Keputusan Pemilihan Laptop Gaming Menggunakan Metode AHP-Topsis - Adhi Mulya, Ananda; Wiwien Hadikurniawati (Fakultas Teknik Universitas Hamzanwadi, 2024)
The process of choosing a gaming laptop involves considering a number of technical and performance factors in addition to budget factors. These factors include battery type, processor quality, graphics card quality, RAM capacity, and storage type. These are the main components that influence the gaming experience. In addition, ergonomics, design and sizing to suit individual preferences must be taken into account. This research aims to reduce the price factor borne by consumers so that it is not the only consideration in choosing a laptop using the AHP-TOPSIS method. The system development methods used are prototypes, modeling using UML and system development using PHP and MySQL. Based on the highest preference value, AHP-TOPSIS recommends that the HP Victus 16-R0017TX gaming laptop be selected as the best option. These suggestions can provide useful direction when choosing a gaming laptop that meets your needs in terms of speed and storage